2015
DOI: 10.1111/nad.12031
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Racism, Numbers Management, and Zero‐Tolerance Policing in New York City

Abstract: Institutional racism is a concept that has gotten into a muddle. Ubiquitous in policing in the UK, but relegated to the margins of discussion in the US, this important and useful idea has been misunderstood on both sides of the Atlantic as a pervasive form of unconscious or cultural bias. This article argues that a clearer distinction is needed between cognitive bias and institutional racism especially with regard to the racial disparities in the enforcement outcomes in New York City. The numbers‐driven manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Despite the success attributed to COMPSTAT, academic studies have not shown a substantive correlation between the program and substantial changes in crime reduction (Eck & Maguire, 2005;Manning, 2008;Weisburd & Eck, 2004). Furthermore, the implementation of the techniques mentioned so far raised questions about police actions against historically stigmatized ethnic-racial groups (Bornstein, 2015;Fabricant, 2011). Digital technological devices such as social media (Fowler, 2017;Graaf & Meijer, 2019;Grimmelikhuijsen & Meijer, 2015;Hu & Lovrich, 2021), body-worn cameras (Bromberg et al, 2018;Lum et al, 2020;McKay & Lee, 2020), big data (Brayne, 2017;Ferguson, 2017), and genetic mapping (Amankwaa & McCartney, 2019;McCartney, 2017) have been adopted in different ways by police organizations and justice systems in general.…”
Section: Technologymentioning
confidence: 99%
“…Despite the success attributed to COMPSTAT, academic studies have not shown a substantive correlation between the program and substantial changes in crime reduction (Eck & Maguire, 2005;Manning, 2008;Weisburd & Eck, 2004). Furthermore, the implementation of the techniques mentioned so far raised questions about police actions against historically stigmatized ethnic-racial groups (Bornstein, 2015;Fabricant, 2011). Digital technological devices such as social media (Fowler, 2017;Graaf & Meijer, 2019;Grimmelikhuijsen & Meijer, 2015;Hu & Lovrich, 2021), body-worn cameras (Bromberg et al, 2018;Lum et al, 2020;McKay & Lee, 2020), big data (Brayne, 2017;Ferguson, 2017), and genetic mapping (Amankwaa & McCartney, 2019;McCartney, 2017) have been adopted in different ways by police organizations and justice systems in general.…”
Section: Technologymentioning
confidence: 99%
“…Critical scholars have described bureaucracy as a patterned outgrowth of potential physical violence, wherein some groups come to wield institutional power over others because it is always backed by the real threat of force, creating structures of vision and value that individuals can become blind to when they are on the more powerful side of these inequities (Eldridge and Reinke 2018; Graeber 2015; Gupta 2012; Herzfeld 1992). Many such descriptions rightly focus on the effects of such bureaucratized potential violence for those outside the institution studied—for instance, the treatment of migrants by state agencies (e.g., Heyman 1995; Sheehan 2018) or of protestors or neighborhood residents by police departments (e.g., Bornstein 2015; Fassin 2013; Feliciano‐Santos 2021). Other studies looking inside institutions also focus on the treatment of “client” or target populations, such as students in schools or patients in clinics and hospitals, to theorize and critique the mechanics of institutionalized power (e.g., George 2016; E. Hull 2012; Shange 2019; Street 2012).…”
Section: Materials Synecdoche and Bureaucratic Violence In Internatio...mentioning
confidence: 99%
“…Bornstein's () examination of institutional racism in the context of zero‐tolerance policing in New York City focuses on “policies of administrative systems” rather than “cognitive racial bias.” For Bornstein, whereas cognitive racial bias highlights “conscious and unconscious associations, negative and positive, about things and people in the world” (52), “institutional racism characterizes a system in which policies that do not necessarily refer to race nevertheless reproduce and sometimes intensify racial disparities and hierarchies” (53). Bornstein also analyzes how purportedly colorblind policies and technologies organize policing in relation to the accumulation of statistics and crime mapping.…”
Section: Anthropologies Of Institutional Racism Across Contextsmentioning
confidence: 99%
“…That is, while analyses of institutional racism seek to challenge ideologies of individualism, there is variability in the ways that embodied individuals are positioned as the locus of action within such analyses. Bornstein's (2015) examination of institutional racism in the context of zero-tolerance policing in New York City focuses on "policies of administrative systems" rather than "cognitive racial bias." For Bornstein, whereas cognitive racial bias highlights "conscious and unconscious associations, negative and positive, about things and people in the world" (52), "institutional racism characterizes a system in which policies that do not necessarily refer to race nevertheless reproduce and sometimes intensify racial disparities and hierarchies" (53).…”
Section: Anthropologies Of Institutional Racism Across Contextsmentioning
confidence: 99%